HCN channelopathy and cardiac electrophysiologic dysfunction in genetic and acquired rat epilepsy models. Issue 4 (4th March 2014) - Powell, Kim L.; Jones, Nigel C.; Kennard, Jeremy T.; Ng, Caroline; Urmaliya, Vijay; Lau, Shannen; Tran, Adora; Zheng, Thomas; Ozturk, Ezgi; Dezsi, Gabi; Megatia, Ika; Delbridge, Lea M.; et al.
Summary Objective Evidence from animal and human studies indicates that epilepsy can affect cardiac function, although the molecular basis of this remains poorly understood. Hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels generate pacemaker activity and modulate cellular excitability in the brain and heart, with altered expression and function associated with epilepsy and cardiomyopathies. Whether HCN expression is altered in the heart in association with epilepsy has not been investigated previously. We studied cardiac electrophysiologic properties and HCN channel subunit expression in rat models of genetic generalized epilepsy (Genetic Absence Epilepsy Rats from Strasbourg, GAERS) and acquired temporal lobe epilepsy (post–status epilepticus SE). We hypothesized that the development of epilepsy is associated with altered cardiac electrophysiologic function and altered cardiac HCN channel expression. Methods Electrocardiography studies were recorded in vivo in rats and in vitro in isolated hearts. Cardiac HCN channel messenger RNA (mRNA) and protein expression were measured using quantitative PCR and Western blotting respectively. Results Cardiac electrophysiology was significantly altered in adult GAERS, with slower heart rate, shorter QRS duration, longer QTc interval, and greater standard deviation of RR intervals compared to control rats. In the post‐SE model, we observed similar interictal changes in several of these parameters, and we also observed consistent and striking bradycardia associated with the onset of ictal activity. Molecular analysis demonstrated significant reductions in cardiac HCN2 mRNA and protein expression in both models, providing a molecular correlate of these electrophysiologic abnormalities. Significance These results demonstrate that ion channelopathies and cardiac dysfunction can develop as a secondary consequence of chronic epilepsy, which may have relevance for the pathophysiology of cardiac dysfunction in patients with epilepsy.